Frequency of Urinary Tract Infections in Diabetic Patients Taking SGLT-2 Inhibitors - Shahbaz, Ali; Ali, Alia; Mahmood, Hafiz Abad; Virk, Muhammad Abdulrehman; Shahnawaz, Iqra; Gul, Mehak (Indus Journal of Bioscience Research, 2025)
Background: Sodium-glucose cotransporter 2 (SGLT-2) inhibitors are widely prescribed for type 2 diabetes mellitus due to their glucose-lowering, cardiovascular, and renal benefits. However, concerns remain regarding an increased risk of urinary tract infections (UTIs), particularly in diabetic patients already predisposed to infections. Evidence from local populations is limited, necessitating focused evaluation. Objective: To determine the frequency of urinary tract infections in diabetic patients taking SGLT-2 inhibitors. Study Design: Descriptive cross-sectional study. Duration and Place of Study: This study was conducted from February 2025 to May 2025 in the Department of Medicine, Shaikh Zayed Federal Postgraduate Medical Institute, Lahore. Methodology: A total of 193 patients aged 20–70 years with type 2 diabetes mellitus receiving SGLT-2 inhibitors for at least three months were enrolled through non-probability consecutive sampling. Demographic characteristics, clinical history, and anthropometric measures were recorded. UTIs were identified based on clinical symptoms such as fever or dysuria within four weeks and confirmed through urine analysis and culture. Results: The mean age was 56.01±9.07 years, with females representing 54.4% of the cohort. The overall frequency of UTIs was 10.9% (n=21). Female gender (p=0.038) and SGLT-2 therapy exceeding 12 months (p=0.010) were significantly associated with higher infection rates. No significant association was found with age, BMI, or residence. Conclusion: UTIs were observed in approximately one-tenth of diabetic patients on SGLT-2 inhibitors, with higher risk in females and long-term users.